TADABBUR SURAH AL-FATIHAH WA TATBIQUHA BI BA'DI QOWAID TADABBUR AL-QUR'AN INDA AL-MAIDANI: Contemplating (Tadabbur) of Surah Al-Fatihah and Its Application with Some of Tadabbur Rules of The Qur’an According to Al-Midani - Muhammad Nur Khalim; Ryan Arif Rahman; Nailul Izzah (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
The Tadabur is the Important to and it is a way to learn the fundamentals of Religion, and it’s required for all people not specific to the mu’min but it’s also for the kafir. Al-Midani has sought to establish some basic rules for Tadabur of The Qur’an and to be a guide him for the facilitate in it.  And Surah Al-Fatihah was of the greatest surah in the Qur’an. The Muslim was read it no less than seventenn times for every day and night, but they are still at the reading level, most of them have not reached to the Tadabur level. They are heedless of it but rather emigrates from it. In this research wants to searches of the rules for The Tadabur of Qur’an from Al-Midani’s book “Qawaid Tadabur al-Amtsal li Kitabillahi ‘Azza Wajalla” and Al-Fatihah is Applied from it, so that Muslims and those who have suffer from it may benefit from it especially in the obligatory prayers. In this paper the researcher used the descriptive and analytical method to collect and analyze of information, and use the library research so the researcher selects with the task rulers from the exiting rules. And the result of this research that Al-Midani was composed the rules with the connection, from the word, verse and surah, and connected to Atsar so connect to linguistic sciences and other sciences that have connection with the Qur’an.